Taxonomic re-assessment of the Australian and New Guinean green-eyed treefrogs Litoria eucnemis, L. genimaculata and L. serrata (Anura: Hylidae) - Richards, Stephen J.; Hoskin, Conrad J.; Cunningham, Michael J.; Mcdonald, Keith; Donnellan, Stephen C. (Zootaxa, 2010)
The green-eyed treefrogs (Litoria eucnemis species-group) are found throughout New Guinea and some of its offshore islands, and in two geographically separated regions in north-eastern Queensland, Australia. We examine the genetic relationships among populations of the complex from across its range and find that populations fall into two major lineages: 1) specimens referable to L. genimaculata from New Guinea and its offshore islands, and L. exophthalmia, and 2) samples referable to L. eucnemis from New Guinea and northern Cape York, Australia, and two lineages from the Wet Tropics of north-eastern Australia that are currently assigned to L. genimaculata. Based on our molecular genetic analyses, morphological assessment of new collections and re-examination of type material, we retain L. eucnemis as currently recognised for northern Cape York populations but resurrect the name L. serrata for the Wet Tropics populations. The degree of reproductive isolation between the two Wet Tropics lineages is being studied currently and so at this point we refer both to L. serrata. The degree of genetic variation observed in L. genimaculata across New Guinea locations and possible paraphyly with L. exophthalmia suggest the presence of additional undescribed species. Reexamination of type material and collection of new specimens, allow us to reassess the status of several other names currently synonymised with L. eucnemis and L. genimaculata. Our observations support the present synonymy of Hyla rhacophorus with L. eucnemis and we remove Nyctimystes loveridgei from the synonymy of L. genimaculata and place it in the synonymy of L. eucnemis.